Social Networking and Libraries: A Review of the Changing Landscape - Kumar, Sandeep (Journal of Advanced Research in Library and Information Science, 2023)
Social networking sites have become a crucial part of people’s life all over the world in the digital age. Libraries, as organisations devoted to the sharing of knowledge and community involvement, have not escaped this change. This review article investigates the relationship between social networking and libraries, looking at how these platforms affect user interaction, information sharing, library services. It also explores the difficulties and opportunities libraries confront as they navigate the new digital environment. This review offers insights into how libraries can effectively leverage the potential of social networking to enhance their roles as contemporary information centres and community hubs by analysing existing literature, case studies, examples. The dynamic interaction between social networking and libraries is examined in this review paper, which also examines the significant effects of digital communication tools on libraries’ conventional functions as information hubs and neighbourhood gathering places. Social media integration has made it possible for libraries to connect with users worldwide and operate outside of their physical boundaries. Libraries may improve their relationships with various groups and successfully meet individual information requirements by developing interactive and collaborative spaces. This review provides useful insights and helpful advice for libraries looking to increase their social media presence by drawing from realworld case studies and best practises. Libraries must use cutting-edge technologies and creative strategies to stay relevant in the digital era as social networking continues to change. By utilising social media, libraries may help to create a future where community participation and lifelong learning are seamlessly integrated, helping people to succeed in a rapidly changing environment.